2015
DOI: 10.1098/rspb.2015.0837
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the life cycle alters expected impacts of climate change

Abstract: Recent models predict contrasting impacts of climate change on tropical and temperate species, but these models ignore how environmental stress and organismal tolerance change during the life cycle. For example, geographical ranges and extinction risks have been inferred from thermal constraints on activity during the adult stage. Yet, most animals pass through a sessile embryonic stage before reaching adulthood, making them more susceptible to warming climates than current models would suggest. By projecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
186
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(193 citation statements)
references
References 47 publications
(78 reference statements)
5
186
0
2
Order By: Relevance
“…Recent studies have highlighted the importance of understanding how heat stress influences early life stages in order to predict population-level consequences of warming (Levy et al, 2016(Levy et al, , 2015. In lizards, the embryos of some species may experience thermally stressful temperatures during summer heatwaves (Levy et al, 2015), which are predicted to occur more frequently in future (Cowan et al, 2014;Hansen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have highlighted the importance of understanding how heat stress influences early life stages in order to predict population-level consequences of warming (Levy et al, 2016(Levy et al, , 2015. In lizards, the embryos of some species may experience thermally stressful temperatures during summer heatwaves (Levy et al, 2015), which are predicted to occur more frequently in future (Cowan et al, 2014;Hansen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Heatwaves have become more common in recent decades (Hansen et al, 2012), and are predicted to increase in frequency in the future (Cowan et al, 2014). Thus, embryos of some lizard species may experience periods of acute thermal stress during development in the future (Levy et al, 2015;Telemeco et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Embryos of endothermic, ectothermic, and oviparous species are also subject to rising environmental temperatures with dramatic developmental and ecological consequences (Gendelman and Roth, 2012; Rosa et al, 2014; Levy et al, 2015; Griffith et al, 2016). Studies on teratogenic effects of heat in mammals have shown that embryos are heat susceptible early and acquire resilience at later developmental stages (Edwards et al, 1997a; Walsh et al, 1997; Hansen, 2009).…”
Section: Introductionmentioning
confidence: 99%